Distance dependent photoacoustics revealed through DNA nanostructures. Issue 42 (18th October 2017) - Joseph, James; Baumann, Kevin N.; Koehler, Philipp; Zuehlsdorff, Tim J.; Cole, Daniel J.; Weber, Judith; Bohndiek, Sarah E.; Hernández-Ainsa, Silvia
Abstract : Photoacoustic enhancement in a distance controlled fashion has been demonstrated through the precise decoration of DNA helices with NIR fluorophore–quencher pairs. Abstract : Molecular rulers that rely on the Förster resonance energy transfer (FRET) mechanism are widely used to investigate dynamic molecular processes that occur on the nanometer scale. However, the capabilities of these fluorescence molecular rulers are fundamentally limited to shallow imaging depths by light scattering in biological samples. Photoacoustic tomography (PAT) has recently emerged as a high resolution modality for in vivo imaging, coupling optical excitation with ultrasound detection. In this paper, we report the capability of PAT to probe distance-dependent FRET at centimeter depths. Using DNA nanotechnology we created several nanostructures with precisely positioned fluorophore–quencher pairs over a range of nanoscale separation distances. PAT of the DNA nanostructures showed distance-dependent photoacoustic signal enhancement and demonstrated the ability of PAT to reveal the FRET process deep within tissue mimicking phantoms. Further, we experimentally validated these DNA nanostructures as a novel and biocompatible strategy to augment the intrinsic photoacoustic signal generation capabilities of small molecule fluorescent dyes.